A-type magmatism in the sierras of Maz and Espinal: A new record of Rodinia break-up in the Western Sierras Pampeanas of Argentina - Colombo, Fernando (2009)
Two orthogneisses have been recognized in the sierras of Espinal and Maz (Western Sierras Pampeanas, NW Argentina) that were emplaced within a Grenvillian metasedimentary sequence. Microcline, plagioclase and quartz are the main rock-forming minerals, with accessory zircon, apatite-(CaF), magnetite, biotite (Fe/(Fe + Mg) = 0.88-0.91), ferropargasite (Fetotal/(Fetotal + Mg) = 0.88-0.89), titanite (with up to 1.61 wt% Y2O3) and an REE-rich epidote. REE-poor epidote and zoned garnet (Ca and Fe3+-rich) are metamorphic minerals, while muscovite, carbonates and chlorite are secondary phases. Texture is mylonitic. Two representative samples are classified as granite (from Sierra de Espinal) and granodiorite/tonalite (from Sierra de Maz) on the grounds of immobile trace elements. Some trace element contents are rather high (Zr: 603 and 891 ppm, Y: 44 and 76 ppm, 10,000 × Ga/Al: 2.39-3.89) and indicate an affiliation with A-type granites (more specifically, the A2 group). Both samples plot in the field of within-plate granites according to their Y and Nb contents. Concordant crystallization ages (zircon U-Pb SHRIMP) are 842 ± 5 and 846 ± 6 Ma, respectively. 87Sr/86Sri (845) ratios are 0.70681 and 0.70666; εNdi (845) values are -1.5 and +0.3 and depleted-mantle Nd model ages (2TDM*) are 1.59 and 1.45 Ga, respectively. These values indicate the involvement of an isotopically evolved source. 2TDM* values are compatible with the presence of inherited zircon crystals of up to 1480 Ma in one of the rocks, thus implying that magmas incorporated material from Mesoproterozoic continental source. This is also indicated by the relatively high contents of Y, Ga, Nb and Ce compared to magmas derived from sources similar to those of oceanic-island basalts. These orthogneisses represent a period of extension at ca. 845 Ma affecting the Western Sierras Pampeanas continental crust that was already consolidated after the Grenvillian orogeny (1.2-1.0 Ga). They are thus a record of the early stages of Rodinia break-up. Metamorphic conditions during the subsequent Famatinian orogenic cycle (ca. 420 Ma, SHRIMP U-Pb on zircon) attained 7.7 ± 1.2 kbar and 664 ± 70 °C. © 2009 Elsevier B.V. All rights reserved.